Biomechanical analysis of grip strength in upper limb rehabilitation (2022)
This research is based on biomechanics as a science that involves concepts of engineering, mechanics, physic, anatomy, physiology, and many others, to study the human body with the desire to solve certain problems that may affect the performance of an individual in their work or personal level. This work is an investigative process in these areas of scientific and applied disciplines, in which the attention is focused on the hand as a valuable tool for the occupational performance of the human being, since through it is possible to touch, move, grasp, or manipulate objects. Injuries to this limb may be due to various causes, which require complex surgeries and long periods of rehabilitation to be reversed. This research highlights the importance of certain physical concepts that must be understood by the rehabilitation expert in order not to affect the surgery and thus guarantee the maximum functionality of the patient at the end of the recovery cycle.